Analisis Makna Foto Makanan (Food Photography) dalam Instagram @jajan_linggau - Dea Nur Maulidya; Fifi Hasmawati; Muhammad Randicha Hamandia (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This thesis is entitled "Analysis of the Meaning of Photography (Food Photography) in Instagram @jajan_linggau". With the formulation of the problem, namely, How to analyze the meaning of food photos (food phtography) in Instagram @jajan_linggau. In this study the researchers chose photography with food photos as objects or what is known as Food Photography. Because, seeing from the photo of the food is able to arouse the appetite and has its own charm. By choosing beautiful colors, it can make food photos look more luxurious and attractive to anyone who sees them, even though basically they have never tried the taste of this food. The qualitative descriptive research method was adopted in this study. This research was conducted using a descriptive approach in accordance with the problems and objectives. A strategy based on a qualitative model was used in this investigation. The meaning referred to in this paper is based on testing using the triangle of meaning from Charles Sanders Pierce's semiotic theory, namely: Representamen/Sign, Interpretant, and Object. In this study, for every food photo (food photography), there is a meaning from the signs displayed in the photo. Its meaning can be found in food images, packaging, the number or name of the product label, as well as other additional elements.